2006
DOI: 10.1073/pnas.0607058103
|View full text |Cite
|
Sign up to set email alerts
|

Hot-spot mimicry of a cytokine receptor by a small molecule

Abstract: Protein-protein complexes remain enticing, but extremely challenging, targets for small-molecule drug discovery. In a rare example described earlier, a high-affinity small molecule, SP4206 (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
114
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(122 citation statements)
references
References 34 publications
(39 reference statements)
8
114
0
Order By: Relevance
“…In spite of their large size disparity, the polar charge distributions of receptor and small molecule interfaces are very similar (Fig. 8b-d) (Thanos et al 2006). In the receptor:IL-2 interaction, the electrostatic fields are defined by a string of acidic groups (glutamate and aspartic acid) on IL-2Ra and a basic Arg 36 that map onto complementary basic (Lys 35, Arg 38) and acidic (Glu 62) patches, respectively, on the surface of IL-2.…”
Section: Comparison Of Small-molecule and Protein Interactions With Il-2mentioning
confidence: 92%
See 2 more Smart Citations
“…In spite of their large size disparity, the polar charge distributions of receptor and small molecule interfaces are very similar (Fig. 8b-d) (Thanos et al 2006). In the receptor:IL-2 interaction, the electrostatic fields are defined by a string of acidic groups (glutamate and aspartic acid) on IL-2Ra and a basic Arg 36 that map onto complementary basic (Lys 35, Arg 38) and acidic (Glu 62) patches, respectively, on the surface of IL-2.…”
Section: Comparison Of Small-molecule and Protein Interactions With Il-2mentioning
confidence: 92%
“…Through these studies, the small-molecule-binding potential of IL-2 was revealed to be more subtle and dynamic than anticipated Hyde et al 2003;Waal et al 2005;Arkin et al 2003;Thanos et al 2003Thanos et al , 2006. The X-ray structure of the IL-2:Ro26-4550 complex displays marked alterations in protein conformation from unliganded IL-2 .…”
Section: Structural Characterization Of Ro26-4550 and The Importance mentioning
confidence: 96%
See 1 more Smart Citation
“…More accurate modeling of side-chain conformational flexibility may also be important for structure-based drug design, when a target protein changes its binding site in response to binding different small molecules 11 . Work by Ranganathan and others [12][13][14][15][16][17][18] has provided intriguing evidence for the existence of "communication pathways" in proteins to facilitate the transmission of signals between allosteric and active sites.…”
Section: Introductionmentioning
confidence: 99%
“…Pharmacological chaperones are small molecules that bind to proteins and stabilize them against thermal denaturation or proteolytic degradation, as well as assisting or preventing certain protein-protein assembly (6)(7)(8). Designing pharmacological chaperones against traditionally "undruggable" protein surfaces relies heavily on the availability of threedimensional structures of the proteins of interests, which are used for the identification of "hotspots" and for the design of ligand mimetic structures (9)(10)(11). A variety of classes of compounds have been shown to be effective pharmacological chaperones, including cofactor mimetics (12), catalytic inhibitors (13), ligand mimetics (14), stabilized helical peptides (15)(16)(17), and small-molecule secondary structure-mimetics (18,19).…”
mentioning
confidence: 99%